2016
DOI: 10.1038/mp.2016.183
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating the mouse thalamus to correct human neurodevelopmental disorders

Abstract: While localizing sensory and motor deficits is one of the cornerstones of clinical neurology, behavioral and cognitive deficits in psychiatry remain impervious to this approach. In psychiatry, major challenges include the relative subtlety by which neural circuits are perturbed, and the limited understanding of how basic circuit functions relate to thought and behavior. Neurodevelopmental disorders offer a window to addressing the first challenge given their strong genetic underpinnings, which can be linked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 91 publications
2
15
0
Order By: Relevance
“…The circuit motifs so revealed will help inform and generate computational models of the role of the cognitive thalamus, beyond that of a relay, in generating behavioral flexibility. In turn these circuit motifs may provide us with specific therapeutic targets for the treatment of cognitive deficits, as seen in neuropsychiatric disorders ( Mukherjee et al, 2019 ; Nakajima et al, 2019a ; Schmitt and Halassa, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The circuit motifs so revealed will help inform and generate computational models of the role of the cognitive thalamus, beyond that of a relay, in generating behavioral flexibility. In turn these circuit motifs may provide us with specific therapeutic targets for the treatment of cognitive deficits, as seen in neuropsychiatric disorders ( Mukherjee et al, 2019 ; Nakajima et al, 2019a ; Schmitt and Halassa, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Motivated by these functional studies, we examined in mice the reciprocal connectivity of MD neurons with their targets in the prelimbic part of the PFC (PL), a hypothesized rodent analogue of primate dorsolateral PFC ( Hoover and Vertes, 2007 ; Vertes, 2004 ). Given the notion that this thalamocortical loop engages in a variety of cognitive control, non-relay functions ( Ferguson and Gao, 2018 ; Schmitt and Halassa, 2017 ), we systematically compared the impact of MD activation on PL activity, as well as its input/output connectivity patterns to those of a classical sensory one. We chose the medial geniculate pathway to primary auditory cortex (A1), given the ease by which this pathway can be controlled in rodents ( Hackett et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…With one exception (McAlonan et al, 2008 ), the identified TRN subnetworks have been demonstrated in rodents; so, comparative studies of other mammalian species are also needed. Even so, in the monkey (McAlonan et al, 2008 ) and mouse (Halassa et al, 2014 ; Wimmer et al, 2015 ; Chen et al, 2016 ), top-down attentional control involves a TRN subnetwork that employs a similar functional mechanism, indicating that at least one such subnetwork is conserved across mammals (Schmitt and Halassa, 2017 ). Pending further interspecies comparisons, our current view of TRN subnetworks indicates considerable functional versatility among TRN neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these contacts are functional is still not known, but the observation suggests that converging inputs of different RGC subtypes may generate novel receptive field features in dLGN, adding a new dimension to thalamic processing. A more nuanced view of the dLGN informs more broadly the role of thalamic circuits in complex sensory and cognitive processes (Litvina and Chen, 2017; Schmitt and Halassa, 2016). …”
Section: Discussionmentioning
confidence: 99%